2016
DOI: 10.1002/nvsm.1558
|View full text |Cite
|
Sign up to set email alerts
|

The Gods can help: exploring the effect of religiosity on youth risk-taking behavior in Indonesia

Abstract: This study explores the impact of intrinsic versus extrinsic religiosity on youth risk‐taking behaviors in Indonesia. Our analysis on Indonesians aged 18–24 shows that intrinsic religiosity has a significant impact on individual's perception of risk‐taking. Understanding the significant role that intrinsic religiosity plays in the lives of youth and their risk‐taking behaviors offers new ways to promote responsibility and risk‐free behavior. We argue that, rather than distancing from religiosity, spirituality … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 82 publications
0
8
0
Order By: Relevance
“…(1) As "*", "**" and "***" we denote that the coefficient is statistically significant at 0.1, 0.05 and 0.01 level respectively. (2) Chi-squared statistic for the null hypothesis "coefficients of CATHOLIC, LUTHERAN, MUSLIM and ORTODOX are not different" in the regression TOBACCO (2) Variables related to adolescent family environment were consistently significant. Not living with both parents increased the risk of smoking any substance.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…(1) As "*", "**" and "***" we denote that the coefficient is statistically significant at 0.1, 0.05 and 0.01 level respectively. (2) Chi-squared statistic for the null hypothesis "coefficients of CATHOLIC, LUTHERAN, MUSLIM and ORTODOX are not different" in the regression TOBACCO (2) Variables related to adolescent family environment were consistently significant. Not living with both parents increased the risk of smoking any substance.…”
Section: Resultsmentioning
confidence: 99%
“…The relationship between religious beliefs and risk taking behaviours has been found significant in young people. 1,2,3,4 Religious communities make up social networks that act as role models, provide social and emotional support, and promote the use of free time engaging in safe activities. 4 Religious practices influence actions and attitudes of persons, including those of adolescents, thereby facilitating the transmission of usually healthy lifestyles 5,6 , that following WHO foundational document must enable "a state of complete physical, mental, and social well-being and not merely the absence of disease or infirmity."…”
Section: Introductionmentioning
confidence: 99%
“…The principles of transforming poison into medicine, earthly desires fueling the quest for enlightenment, and oneness of life and its environment can be leveraged by nonprofit marketers to make a positive impact in the areas of management of mental health problems, stress, and depression, as well as crime, delinquency, and substance abuse. Arli et al () argue that, rather than distancing from religiosity, spirituality, and faith, social marketers and public policy makers should be working closely with religious institutions to enact social change among the youth. The Nichiren Buddhist perspective that each and every person has limitless positive potential and the power to change his or her life for the better that we can all transform our innate negativities into positive attributes, our sorrows into creating positive value, and our happiness for ourselves and others can be applied as guiding principles when reaching out to customer segments who are deeply suffering.…”
Section: Methodsmentioning
confidence: 99%
“…The role played by spirituality and religion in affecting consumption has been well recognized in the literature (Arli, Cherrier, & Hari Lasmono, ; Casidy, Phau, & Lwin, ; Choi, Kale, & Shin, ; Stillman, Fincham, Vohs, Lambert, & Phillips, ). Religion has been acknowledged as one of the most cultural forces and influences on consumption (Cornwell et al, ; Lindridge, ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Religiosity also does not influence EC, which is in line with research conducted by [39] on Indonesian. Research conducted by [40] showed a negative relationship between religiosity and ethics among Indonesian Muslims and young people (18-24 years). Despite being a religious country [13,14], Indonesia is also the second-largest country in the world after China, which contributes to environmental pollution through plastic [41].…”
Section: Hypothesis Testingmentioning
confidence: 99%